Pengaruh Gaya Kepemimpinan Transformasional Dan Iklim Organisasi Terhadap Kapabilitas Inovasi Organisasi PDAM Tirta Dharma Kabupaten Kolaka - Siska Farlina; Almansyah Rundu Wonua; Ismanto Ismanto (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2023)
This research aims to find out how to determine the influence of transformational leadership style and organizational climate on the organizational innovation capabilities of the Regional Drinking Water Company (PDAM) Tirta Dharma, Kolaka Regency. This research uses explanatory research using quantitative research methods. Data collection techniques are literature study, distribution of questionnaires. Furthermore, the population in this study was all employees of PDAM Tirta Dharma Kolaka Regency. The sampling technique uses the census method. Testing the research instrument uses validity and reliability tests with SPSS 25.0. Meanwhile, the data analysis technique uses Partial Least Square (PLS) using the Smart-PLS application. Based on the research results, it was concluded that the Transformational Leadership Style and Organizational Climate had a Positive and Significant influence on the Organization's Innovation Capability.